Playground: just a Place to Go out or a Space for Child Development? - Kotliar, I.A.; Sokolova, M.V. (Psihologo-pedagogičeskie issledovaniâ, 2019)
The article discusses the relevance of modern play spaces to the tasks of the mental and physical child development, as well as modern approaches to the examination of children's outdoor play environment. A historical analysis of changes in domestic and foreign theories about ideas - what kind of playground children need, also empirical studies of child behavior at different play environment allow us to highlight the main lines of psychological and pedagogical analysis of play spaces. New standards in the field of education and development, as well as in designing educational environment, the request of teachers and designers (architects, engineers) makes relevant to work out the methodological support of the creation of play environment. Interdisciplinary approach and dialogue in this area will allow us to solve the problem of designing such play environment that meets the tasks of the child development. В статье рассматриваются вопросы соответствия современных игровых сред и их частного случая — детских площадок — задачам психического и физического развития ребенка, а также современные подходы к экспертизе детских уличных игровых сред. Исторический анализ изменения отечественных и зарубежных представлений о том, какая площадка нужна детям, полученные в эмпирических исследованиях факты о поведении детей в разных игровых средах позволяют выделить основные линии психолого-педагогического анализа игровой среды. Появление новых нормативов в области воспитания и развития, а также в области проектирования образовательной среды, запрос педагогов-практиков и проектировщиков (архитекторов, инженеров) делают актуальным методологическое и методическое сопровождение процессов создания игровых сред. Междисциплинарный подход и диалог в этой области позволят решить задачу создания игровых сред, отвечающих задачам психического и физического развития ребенка.